2012
DOI: 10.1080/10255842.2011.571678
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based assessment of movement difficulties in Parkinson's disease

Abstract: The prevalence of Parkinson's disease (PD) is increasing due to an ageing population. It is an unpredictable disease which requires regular assessment and monitoring. Current techniques used to assess PD are subjective. Clinicians observe movements made by a patient and subsequently rate the level of severity of, for example tremor or slowness of movement. Within this work, we have developed and evaluated a prototype computer-based assessment tool capable of collecting information on the movement difficulties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the present work, the effects of VA were evaluated in the experimental model of PD, consisting of a unilateral striatal injection of the 6-OHDA neurotoxin in rats. An attempt was made to correlate the VA neuroprotective action to its anti-inflammatory effects and these with neurodegenerative diseases, mainly PD, are already observed by us and others [ 27 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the effects of VA were evaluated in the experimental model of PD, consisting of a unilateral striatal injection of the 6-OHDA neurotoxin in rats. An attempt was made to correlate the VA neuroprotective action to its anti-inflammatory effects and these with neurodegenerative diseases, mainly PD, are already observed by us and others [ 27 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 technologies assess PD-related features in addition to bradykinesia [ 16–19, 21–25, 27–30, 34, 36, 37, 40–42, 44, 47, 49, 53, 55, 57, 58, 60, 62 ]. Among these, 7 measured dyskinesia [ 16, 19, 25, 41, 64–66 ], 16 measured tremor [ 17, 23, 25, 27, 28, 30, 47, 49, 58, 67–73 ], 12 assessed gait [ 20, 23, 24, 29, 46, 66–72 ], 6 assessed rigidity [ 29, 36, 47, 58, 74, 75 ], 2 assessed speech [ 17, 24 ], 3 assessed cognition [ 27, 30, 76 ], and 3 assessed sleep [ 30, 77, 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating the feasibility of online assessment have identified that PD symptoms such as hypophonia (soft voice) may cause clinical raters difficulty in hearing the participant clearly, and symptoms of tremor, rigidity, dyskinesia, and bradykinesia may cause the participants difficulty using computers when needing steady hand movements to navigate a mouse [12, 20]. The results from this study, from the content analysis of clinical rater and participant feedback, did not indicate that PD symptoms impacted on the participant's ability to engage in any aspects of the videoconference assessment.…”
Section: Discussionmentioning
confidence: 99%